Distribution and Antioxidant Efficiency of Resveratrol in Stripped Corn Oil Emulsions - Sonia Losada-Barreiro; Marlene Costa; Carlos Bravo-Díaz; Fátima Paiva-Martins (MDPI AG, 2014)
We investigated the effects of resveratrol (RES) on the oxidative stability of emulsions composed of stripped corn oil, acidic water and Tween 20 and determined its distribution in the intact emulsions by employing a well-established kinetic method. The distribution of RES is described by two partition constants, that between the oil-interfacial region, POI, and that between the aqueous and interfacial region, PWI. The partition constants, POI and PWI, are obtained in the intact emulsions from the variations of the observed rate constant, kobs, for the reaction between the hydrophobic 4-hexadecylbenzenediazonium ion and RES with the emulsifier volume fraction, ФI. The obtained POI and PWI values are quite high, PWI = 4374 and POI = 930, indicating that RES is primarily located in the interfacial region of the emulsions, %RESI > 90% at ФI = 0.005, increasing up to 99% at ФI = 0.04. The oxidative stability of the corn oil emulsions was determined by measuring the formation of conjugated dienes at a given time in the absence and in the presence of RES. The addition of RES did not improve their oxidative stability in spite that more than 90% of RES is located in the interfacial region of the emulsion, because of the very low radical scavenging activity of RES.